Epithelial extracellular vesicles induce inflammation and neutrophil activation in the Pseudomonas aeruginosa infected cystic fibrosis bronchial epithelium - Hirsch, Meghan June; Tsai, Kuen-You; Jones, Luke I.; Morales, Angela N.; McIntire-Ray, Hannah J.; Howze IV, Patrick H.; Barnes, Jarrod W.; Margaroli, Camilla; Genschmer, Kristopher; Krick, Stefanie (Frontiers in Immunology, 2026)
IntroductionCystic fibrosis (CF) is an autosomal recessive disorder, which manifests in many organ systems including the lungs. Chronic inflammation is a hallmark of CF lung disease leading to bronchiectasis and lung function decline. This is worsened by airway colonization and recurrent infections due to opportunistic pathogens such as Pseudomonas aeruginosa [PA], but the crosstalk between host-bronchial epithelium and immune system has been under characterized. Extracellular vesicles have been found to mediate intercellular crosstalk in different lung diseases and EVs have been shown to be increased in the bronchoalveolar fluid of CF patients. We hypothesize that EVs from PA-infected CF bronchial epithelial cells can modulate pro-inflammatory cytokines and neutrophil migration and activation in an autocrine and paracrine manner.MethodsCF bronchial epithelial cells (CFBEs) and control bronchial epithelial cells (16HBEs) were infected with PA for 24 hours followed by EV isolation, which were used to treat uninfected CFBE and 16HBEs to assess expression and secretion of pro-inflammatory markers. In addition, the effects of EVs on neutrophil migration and activation were determined as well as the role of CFTR deficiency by using CFTR modulator therapy (Elexacaftor/Tezacaftor/Ivacaftor).ResultsEVs derived from PA infected CFBEs (EVpPAs) increased IL-6, IL-8, and TNFα expression and neutrophil activation in CFBEs but not in 16HBEs. Interestingly, the effect of EVpPAs on inflammation was not attenuated by pre-treatment with ETI.DiscussionEVs from the PA-infected CF bronchial epithelium seem to facilitate an autocrine and paracrine pro-inflammatory response that is not attenuated by ETI treatment, suggesting a novel contribution of EVs to the chronic inflammatory phenotype observed in the PA-infected CF lung.